Cryptography With Compressive Sensing Orthogonal Matching Pursuit Method - Atar, Ertan; Ersoy, Okan K.; Ozyilmaz, Lale (IEEE, 2015)
Compressive sensing is a new technique of reconstructing a signal with much less number of measurements than what is required by the sampling theorem. Sparse signals, detection (measurement) matrices are obtained with the aid of measurements stored into vectors. If the signal is sparse enough, the original signal can be recovered successfully. In this study, compressive sensing Orthogonal Matching Pursuit (OMP) algorithm is used, and applied to symmetric cryptography application. Since OMP is a compressive sensing method, both compressive sensing and cryptographic encyrption/decyrption are achieved simultaneously. Two-times complex reinforced encryption and decryption cryptography was also achieved with the new method.
Keywords: Compressive sensing; orthogonal matching pursuit algorithm; cryptography; discrete cosine-III transform; complex key; data size reduction; Engineering; Telecommunications